2020
DOI: 10.1186/s13011-020-00268-4
|View full text |Cite
|
Sign up to set email alerts
|

Khat induced psychotic disorder: case report

Abstract: Background: Khat (Catha edulis) is a stimulant leaf khat comes from a tree which grows in countries bordering the Red Sea which are along the east coast of Africa and in west Asia. The psycho-active component within these leaves is cathinone. In Ethiopia, Khat is chewed routinely by users for its euphoric effects and as a recreational drug, and chewing khat has an important role as well in both traditional and religious ceremonies. In this case report, we describe the case of a 33-year-old male patient present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Moreover, studies show that khat affects driving, social behavior, and work performance. It has been associated with homicide, notably in mentally ill people [ 11 , 48 , 53 , 56 , 57 ], and two reported homicides have been linked to khat consumption [ 56 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies show that khat affects driving, social behavior, and work performance. It has been associated with homicide, notably in mentally ill people [ 11 , 48 , 53 , 56 , 57 ], and two reported homicides have been linked to khat consumption [ 56 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to investigate the potential link between excessive khat use and the risk of mental health disorders such as psychosis (30)(31)(32)(33)(34), depression, stress, anxiety (34,35), mental distress (36), suicidal ideation (37), and paranoid ideation (38). A systematic review and meta-analysis of 35 studies found that the odds of psychotic symptoms among khat users were 2.22 times greater than the odds among non-khat users (39).…”
Section: Mental Health Disordersmentioning
confidence: 99%
“…In 2018, his illness worsened to the extent he attempted to kill himself using a rope in the absence of a depressed mood. After he agreed to quit khat use, his illness improved in two weeks of his sobriety from khat consumption [ 17 ]. This case demonstrates that the use of excess khat above two bundles for a prolonged duration can manifest with psychotic episodes.…”
Section: Reviewmentioning
confidence: 99%